Updated severity and prognosis score of pulmonary alveolar proteinosis: A multi-center cohort study in China - Bai, Jiu-Wu; Huang, Jian-nan; Shi, Shen-yun; Ge, Ai; Lu, Hai-wen; Sun, Xiao-li; Gu, Shu-yi; Liang, Shuo; Cheng, Ke-bin; Tian, Xin-lun; Xiao, Yong-long; Xu, Kai-feng; et al. (Frontiers in Medicine, 2023)
Background The high-resolution computed tomography (HRCT) score is an important component of the severity and prognosis score of pulmonary alveolar proteinosis (SPSP). However, the HRCT score in SPSP only considers the extent of opacity, which is insufficient. Methods We retrospectively evaluated HRCT scores for 231 patients with autoimmune pulmonary alveolar proteinosis (APAP) from three centers of the China Alliance for Rare Diseases. The SPSPII was created based on the overall density and extent, incorporating the SPSP. The severity of APAP patients was assessed using disease severity scores (DSS), SPSP, and SPSPII to determine the strengths and weaknesses of the different assessment methods. We then prospectively applied the SPSPII to patients before treatment, and the curative effect was assessed after 3 months. Results The HRCT overall density and extent scores in our retrospective analysis were higher than the extent scores in all patients and every original extent score severity group, as well as higher related to arterial partial oxygen pressure (PaO2) than extent scores. The mild patients accounted for 61.9% based on DSS 1–2, 20.3% based on SPSP 1–3, and 20.8% based on SPSPII 1–3. Based on SPSP or SPSPII, the number of severe patients deteriorating was higher in the mild and moderate groups. When applied prospectively, arterial PaO2 differed between any two SPSPII severity groups. The alveolar-arterial gradient in PaO2 (P[A-a]O2), % predicted carbon monoxide diffusing capacity of the lung (DLCO), and HRCT score were higher in the severe group than in the mild and moderate groups. After diagnosis, mild patients received symptomatic treatment, moderate patients received pure whole lung lavage (WLL) or granulocyte-macrophage colony-stimulating factor (GM-CSF) therapy, and severe patients received WLL and GM-CSF therapy. Importantly, the SPSPII in mild and severe groups were lower than baseline after 3 months. Conclusion The HRCT density and extent scores of patients with APAP were better than the extent score. The SPSPII score system based on smoking status, symptoms, PaO2, predicted DLCO, and overall HRCT score was better than DSS and SPSP for assessing the severity and efficacy and predicting the prognosis. Trial registration ClinicalTrial.gov, identifier: NCT04516577.